Application Of Polyurethane Injection For Rehabilitation Of The Maingate Of A Deep Single Entry Longwall Mine - Kevin MacPherson (International Conference on Ground Control in Mining, 1999)
After 34km of roof bolted drivage the first fall of ground occurred at the Phalen Colliery in the maingate of the 8th East longwall panel. The fall occurred over the stage loader as the wall approached an area of poor roof geology. This area had developed a severe cutter since initial drivage and the longwall had yet to mine through 500m of even worse conditions. This paper describes the cause of the poor roof conditions, the use of polyurethane resin injection and cable bolting to re-stabilize the roof outby the fall, and the measurement of roof movement and performance subsequent to the continuation of mining under the rehabilitated roof.